The biography of ancient Israel : national narratives in the Bible - Pardes, Ilana (Contraversions ;, 2000)
The nation--particularly in Exodus and Numbers--is not an abstract concept but rather a grand character whose history is fleshed out with remarkable literary power. In her innovative exploration of national imagination in the Bible, Pardes highlights the textual manifestations of the metaphor, the many anthropomorphisms by which a collective character named "Israel" springs to life